Adnexal Torsion in Ovarian Hyperstimulation Syndrome in Early Pregnancy: A Diagnostic Challenge - Regmi, Pradeep R; Amatya, Isha; Poudel, Atit (Journal of Institute of Medicine Nepal, 2020)
Adnexal torsion in ovarian hyperstimulation syndrome (OHSS) is rare but serious complication in pregnancy. It is more common in assisted reproductive techniques. Delay in diagnosis and treatment results in functional loss of ovary as well as termination of pregnancy. In this report, we are presenting a case of 27 years female with subfertility who conceived after ovulation induction presented at 7 weeks 6 days period of gestation with ovarian hyperstimulation associated with adnexal torsion. Later, she was treated with laparoscopic salpingo-oophorectomy.